Earplug Umbilicoplasty: A Simple Method to Prevent Umbilical Stenosis in a Tummy Tuck - Kachare, Swapnil (Eplasty, 2019)
Objective: An aesthetically pleasing umbilicus is a vital component of patient satisfaction following an abdominoplasty. An umbilicus that is moderate to small is desired to achieve the best aesthetic result, but a small umbilicus has potential for stenosis. This article presents a method for umbilical stenting that creates a modest umbilicus, while preventing stenosis. Methods: All patients underwent abdominoplasty with an umbilical reconstruction using an inverted U-flap method between 2015 and 2017. An earplug was placed into the umbilicus at 2 weeks postoperatively for a total of 4 to 6 week. Patients were evaluated subjectively on the aesthetic outcome. Results: Twenty-one female patients were evaluated 6 weeks postsurgery. In all cases, both the patient and the surgeon were 100% satisfied with the final size. Umbilical size ranged from 1.8 to 2.2 cm. Conclusions: Use of an earplug for umbilical stenting is a simple and reproducible method to create an aesthetically pleasing umbilicus and avoid stenosis.